Code-Mixing in Action: How Indonesian Fans Use English Loanwords in Korean Fandom Tweets - Azzahra, Inggri; Marccela, Tina (Proceedings Series on Social Sciences & Humanities, 2025)
The phenomenon of code-mixing, particularly the integration of English words into Indonesian tweets among Korean fan communities, demonstrates the interesting intersection of language, culture and identity. As global fandom expands, a unique linguistic landscape is created where fans express their identities and affiliations through language mixing. This study aims to explore how Indonesian fans of Korean pop culture use English-derived words in their tweets, reflecting both their engagement with global media and the dynamics of local linguistic practices. This research uses a descriptive qualitative method. The purposive sampling method is used in this research. The purposive sampling method is used in this study to analyze all sentences written by starfess. The researchers classified the data based on the type and reason of code mix. Researchers found code mixes in various types, for the types of code mixes found in @starfess tweets, researchers analyzed using Suwito's theory. The types put forward by Suwito such as words, and idioms. Overall, this study has opened up research directions while offering in-depth information about the phenomenon of code-mixing on Twitter. Future research could investigate the psychological underpinnings of why people participate in code-mixing online or compare analysis on other platforms. The linguistic methods used by digital communication users will also change over time, requiring constant scientific attention to understand these developments and their wider impact on society and communication.